A Review of Ice Core Drilling in Cave Environment – Challenges, Achievements and Future Directions - Kern, Zoltan; Perșoiu, Aurel (Frontiers in Earth Science, 2022)
Worldwide, more than 141 m of ice cores has been extracted from 20 cave ice deposits, with the drilling projects focusing mainly in Central European caves. The fact that half of the cave ice cores (3 out of 6) published in 2020 represent non-European localities, however, predicts that an increasing number of cave ice drilling projects will be carried out in the near future in other geographical areas hosting ice caves. Based on the gathered experience the most commonly encountered technical challenge of ice-core drilling problems in cave environment is englacial rocky/woody debris. The complex stratigraphy of cave ice deposits represents a crucial methodological problem. We propose an (CISAD - Cave Ice Sedimentary Architecture and Deposition) approach to take into consideration of the stratigraphic peculiarities of the investigated cave ice deposit and additional crucial meta-data before establishing the location of a drilling site best-suited to obtain the highest quality paleoenvironmental data.